Upaya Meningkatkan Hasil Belajar IPA Melalui Model Pembelajaran Kooperatif Tipe Umpan Balik pada Siswa Kelas IV B SD Negeri 64/IV Kota Jambi - Susirah Susirah (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
The background of this research is that science learning in general at the elementary school level is mostly carried out with the lecture method, teachers are reluctant to use learning media or teaching aids, on the grounds that the use of teaching aids or learning media requires a large amount of money and is not practical. Without realizing it, that is what causes the students' learning activeness and results of science to be low. The purpose of this action research is to know the improvement of science learning outcomes after the use of the feedback type cooperative learning model in class IV B 64 / IV Jambi Elementary School students. The subjects in this study amounted to 30 students. This study uses classroom action research conducted in two rounds. Each round consists of four stages, namely: design, activity and observation, reflection, and revision. Data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of data analysts, it was found that student learning outcomes experienced a significant increase. the increase in learning outcomes was marked by an increase in student learning completeness in each cycle, namely the pre cycle (59.50%), the first cycle (68.33%) and the second cycle (80.75%). From the results of the data analysis it can be concluded that the Cooperative Cooperative Type Feedback type learning model can positively influence the increase in activity and learning outcomes of class IV B students of 64 / IV Jambi City Elementary School, and this learning model can be used as an alternative in science learning next.